Development of a mathematics e-module using GeoGebra and LiveWorksheets with discovery learning model to enhance problem-solving skills - Dini Dahlia; M. Rosyadi; Almas Zati Hulwani; Heni Pujiastuti (Universitas Sarjanawiyata Tamansiswa, 2024)
The study aims to produce e-module teaching materials based on Discovery Learning, supported by GeoGebra and LiveWorksheets, as well as to determine whether this e-module is valid, practical, and has a potential effect on students' problem-solving abilities. The research method used is Research and Development (R&D) with an ADDIE design. The research process consists of five stages: (1) Analysis (analysis of material needs, material analysis, and analysis of student characteristics); (2) Design (design or product framework to be made as an initial overview); (3) Development (development of the e-module and preparation of instruments to be used for valid, practical, and effective assessments); (4) Implementation (product review to be developed in classroom learning); (5) Evaluation (the product will be revised based on feedback given by the students to ensure the quality of the developed product is appropriate and adequate). The e-module learning materials were given to class X students of Senior High School. The results of the expert material validation obtained a percentage evaluation of 88%, indicating valid criteria. The test results showed that this e-module received a positive response from the students with an average percentage evaluation of 85%, categorizing it as highly effective. The material validation resulted in an 88% evaluation percentage, indicating valid criteria. The students' validation results obtained an 85% assessment percentage, also indicating valid criteria. The development of this module is worthy and suitable for use in schools by teachers to enhance students' conceptual understanding of quadratic equations and quadratic functions. Additionally, the module can develop critical thinking and problem-solving skills, which are crucial in 21st-century education.